A preliminary design tool for volumetric buildings. (17th May 2022) - Lim, Robert Z. C.; Looi, Daniel T. W.; Tsang, Hing‐Ho; Wilson, John L.
Summary: Volumetric building (VB) is a type of off‐site construction to move towards high productivity construction. Literature review shows that there are only few models for upstream feasibility study for VB, while many researchers delved into advanced structural engineering aspects of VB modeling (i.e., downstream detailed and technical design). However, there is a lack of guidance for the preliminary design of VB, which is an essential stage that falls in between upstream feasibility study and downstream detailed and technical design. Hence, this paper is written to fill that gap by proposing a new design tool for VB, anchored upon the "desire path" philosophy, which is often used in urban planning, that is, natural formations evident from preceding experiences. Literature review also shows that a comprehensive VB database is not available. Hence, a new database is collected with 31, 185 units of modules and 911 module types, sourced from VB projects worldwide to provide a broad global overview. The proposed tool has a systematic framework of a four‐quadrant plot for preliminary VB design, enabling designers to determine the number of modules, size of modules, massing typology, and module construction material through new empirical relationships.